Integrated fermentation and anaerobic digestion of primary sludges for simultaneous resource and energy recovery: Impact of volatile fatty acids recovery. (December 2020) - Bahreini, Gholamreza; Elbeshbishy, Elsayed; Jimenez, Jose; Santoro, Domenico; Nakhla, George
Graphical abstract: Highlights: VFA recovery and dewaterability of fermented sludges improved at long SRTs. pH-controlled fermentation improved VFA yields by 72–93% Cellulose contributed up to 38% and 41% of methane production from sludges. VFA recovery can save 7.2–7.6% of sludge handling costs in a 100 MLD WWTP. Integrated fermentation-digestion system economically outperformed single digestion. Abstract: This research assessed the impact of volatile fatty acids (VFA) recovery and biomethane potential in an integrated fermentation-digestion process with a single stage digestion of primary and rotating belt filtration (RBF) sludges. Implementing semi-continuous fermentation at 1, 2, and 4 days solids retention time (SRT) showed a direct impact on the hydrolysis and VFA recovery which increased as SRT increased, while also improving the dewaterability by reducing the concentrated sludge volume index of the processed sludge. pH-controlled fermentation was effective improving the VFA yields by up to 93% and 72% at pH 9 (relative to no pH control), for RBF and primary sludges, respectively; although fermentation at pH 6 (optimum) showed promise for enhancing VFAs while lowering the required chemicals significantly. Although cellulose constituted only 21.0% and 29.5% of the TSS in primary and RBF sludges, it contributed 38–41% of the methane production for the two sludges, respectively. Experimental results of integrated fermentation-digestion and single stage digestion processes were incorporated in techno-economic analysis. Results confirmed the economic viability of fermentation with payback periods of 2.7 ± 1.1 years (RBF), and 3.6 ± 2.7 years (PS), while also revealed that VFA recovery could save up to 7.2 ± 2.0% (RBF), and 7.6 ± 2.7% (PS) of the respective total sludge handling and disposal costs, despite an average of 12.7% and 8.4% decrease in biogas production due to VFA extraction in the integrated systems of RBF and primary sludges, respectively. Overall, the integrated fermentation-digestion system economically outperformed the single stage digestion for both sludge types under all studied scenarios.